The efficacy and safety of anlotinib combined with platinum-etoposide chemotherapy as first-line treatment for extensive-stage small cell lung cancer: A Chinese multicenter real-world study - Zheng, Hao-Ran; Jiang, Ai-Min; Gao, Huan; Liu, Na; Zheng, Xiao-Qiang; Fu, Xiao; Ruan, Zhi-Ping; Tian, Tao; Liang, Xuan; Yao, Yu (Frontiers in Oncology, 2022)
Background Patients with extensive-stage small-cell lung cancer (ES-SCLC) have high recurrence rates and bleak prognosis. This multicenter real-world study aimed to explore the efficacy and safety of anlotinib combined with platinum-etoposide chemotherapy as the first-line treatment of ES-SCLC. Methods Pathologically confirmed ES-SCLC patients receiving anlotinib plus platinum-etoposide chemotherapy as the first-line treatment were enrolled in this retrospective study. The primary endpoint of this study was progression-free survival (PFS), and secondary endpoints included overall survival (OS), objective response rate (ORR), disease control rate (DCR), and adverse reactions. The Cox regression analyses were employed to investigate the independent prognostic factors for OS and PFS of these individuals. Results In total, 58 patients were included in this study. The median PFS was 6.0 months [95% confidence interval (CI): 3.5-8.5], and the median OS was 10.5 months (95%CI 8.7-12.3). Thirty-four patients achieved partial response (PR), 18 patients achieved stable disease (SD), and 6 patients achieved progressive disease (PD). The ORR and DCR were 58.6% and 89.6%. The main treatment-related adverse reactions were generally tolerated. Myelosuppression (44.8%) was the most common adverse reaction, followed by hypertension (41.4%), fatigue (34.5%), gastrointestinal reaction (32.7%), and hand-foot syndrome (24.1%). Multivariate analysis showed that post-medication hand-foot syndrome [PFS 8.5 vs. 5.5 months, Hazards Ratio (HR)=0.23, 95%CI 0.07-0.72, P =0.012] was the independent predictor of PFS, and hypertension (OS 15.9 vs. 8.3 months, HR=0.18, 95%CI 0.05-0.58, P =0.005) was the independent predictor of OS. Conclusion Anlotinib combined with platinum-etoposide chemotherapy as the first-line treatment for ES-SCLC appears to be effective and well-tolerated in the real-world. Well-designed large-scale prospective studies are urgently needed in the future to verify our findings.